Yield and yield contributing attributes of rice (Oryza Sativa L.) under different planting dates in boro season (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The experiment was conducted in the experimental field of Sher-e-Bangla Agricultural University, Dhaka-1207 to find out the yield and yield contributing attributes of rice varieties under different planting times. The experiment comprised of two factors- factor a: Planting time (2): T1: 24th January planting; T2: 23th February planting and factor b: Rice variety (5): V1: BRRI dhan29; V2: BRRI hybrid 2; V3: Hera 2; V4: Tia and V5: Taj 1. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Among the different planting time and varieties, 24th January planting and Hera 2 were found superior in terms of yield and yield contributing attributes of rice varieties. Irrespective of planting times, the highest panicle length (24.64 cm), number of effective tillers  hill-1(13.33), filled grains panicle-1 (83.17), 1000-grain weight (25.14 g), grain yield (4.30 t ha-1), straw yield (5.21 t ha-1), biological yield (9.43 t ha-1) and harvest index (45.89%) were achieved. However, Hera 2 provided the highest grain yield (4.64 t ha-1) at 24th January planting compared to other combination. It meant that Hera 2 performed well with 24th January planting.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 162-169